(untitled) (Bangladesh Pharmaceutical Journal, 2019)
The objective of this review is to consider the phytoconstituents from six species under the genus Amaranthus (A. retroflexus, A. spinosus, A. viridis, A. caudatus, A. hypocondriacus and A. tricolor). A total of sixty five (1-65) phytoconstituents with chemical structures have been reported in this study. A. retroflexus consists of high number of reported phytoconstituents. Bangladesh Pharmaceutical Journal 22(1): 117-124, 2019